Experimental and Numerical Studies on Ballistic Laminates on the Polyethylene and Polypropylene Matrix. (15th November 2017) - Mayer, P.; Pyka, D.; Jamroziak, K.; Pach, J.; Bocian, M.
Abstract : The paper analyzes the issues relating to the applicability of innovative material systems for flexible composite armors. The authors made several samplings of aramid fibers (Kevlar 49) by replacing the epoxy resin base, which is often described in the literature, with the thermoplastic matrix -polyethylene (HDPE) and polypropylene (PP). The samples were fired with .38 Special Full Metal Jacketed (FMJ) ammunition produced by the S&B Company, and then the process of firing was modeled in the ABAQUS program. The advantages and disadvantages of the new material system including the possibility of its use in the construction of hybrid composite armors have been presented on the basis of the results of numerical analyses and ballistic tests.